518 Epigenetic dysfunction of terminally exhausted tumor infiltrating T cells. (10th December 2020) - Ford, Rhodes; Vignali, Paolo; Rittenhouse, Natalie; Scharping, Nicole; Frisch, Andrew; Delgoffe, Greg; Poholek, Amanda
Abstract : Background: Tumor-infiltrating CD8+ T cells have been characterized by their exhausted phenotype with decreased cytokine expression and increased expression of co-inhibitory receptors, such as PD-1 and Tim-3. These receptors mark the progression towards exhaustion from a progenitor stage (PD-1Low) to a terminally exhausted stage (PD-1+Tim-3+). While the epigenetics of tumor-infiltrating T cells are unique compared to naïve, effector, and memory populations, how the chromatin landscape changes during this progression has not been described. Methods: Using a low-input ChIP-based assay called Cleavage Under Targets and Release Using Nuclease (CUT&RUN), we profiled the histone modifications at the chromatin of tumor-infiltrating CD8+ T cell subsets to better understand the relationship between the epigenome and the transcriptome as TIL progress towards terminal exhaustion. Results: We have identified two epigenetic characteristics unique to terminally exhausted cells. First, we found a substantial increase in the number of genes that exhibit bivalent chromatin marks, defined by the presence of both activating (H3K4me3) and repressive (H3K27me3) epigenetic modifications that inhibit gene expression. In contrast to stem cells which exhibit bivalency, bivalent genes in terminally exhausted T cells are not associated with plasticity and represent aberrant hypermethylation in response to tumor hypoxia. Secondly, we have also identified a unique set of enhancers, characterized by H3K27ac that do not drive gene expression. These enhancers are enriched for AP-1 transcription factors, whereas enhancers that correlate with gene transcription are enriched for nuclear receptor (NR) transcription factors. Intriguingly, while most AP-1 and NR transcription factors are not expressed in terminally exhausted cells, we found that Batf, an inhibitory AP-1 family member, and Nr4a2, a NR known to promote both exhaustion and modify chromatin were specifically expressed in terminally exhausted cells. These data suggest the balance of Batf and Nr4a2 may modulate the enhancer landscape to promote terminal exhaustion, while hypoxia simultaneously promotes hypermethylation and gene repression. Conclusions: Our study defines for the first time the features of epigenetic dysfunction in tumor-mediated T cell exhaustion and deepens our understanding of the epigenetic regulation of gene expression. These observations are the bases for future work that will elucidate that factors that drive progression towards terminal T cell exhaustion at the epigenetic level and identify novel therapeutic targets to restore effector function of tumor T cells and mediate tumor clearance.